Comparison of steam technology and a two-step cleaning (water/detergent) and disinfecting (1,000 resp. 5,000 ppm hypochlorite) method using microfiber cloth for environmental control of multidrug-resistant organisms in an intensive care unit - Oztoprak, Nefise; Kizilates, Filiz; Percin, Duygu (German Medical Science GMS Publishing House, 2019)
Aim: The aim of this prospective observational study was to evaluate the impact of two cleaning and disinfecting methods and the use of steam against methicillin-resistant , vancomycin-resistant , carbapenem-resistant and multidrug-resistant (MDR) in a tertiary referral hospital. Methods: McFarland 0.5 suspensions (content 1.5 x 10 cfu/ml) of four challenge bacterial species were prepared and used to inoculate different sites in three ICU rooms. One of the following methods was used in each room: steam technology (Tecnovap Evo 304) resp. cleaning with microfiber cloths, soaked with detergent and water, thereafter disinfection with 1,000 ppm hypochlorite or the same procedure with 5,000 ppm hypochlorite. Qualitative microbiology and ATP bioluminescence were performed before and after cleaning with each method. The Wilcoxon test was used for paired samples to check for ordinal variables. The cost of each cleaning method was analyzed. Results: Environmental cleaning with steam technology was found to be as effective against MDR microorganisms as a two-step cleaning process (water/detergent and disinfecting with 1,000 resp. 5,000 ppm hypochlorite) in ICUs. No bacterial growth was detected after any of the three cleaning methods. Steam technology was 76% and 91% cheaper than using 5,000 ppm and 1,000 ppm hypochlorite, respectively.Conclusions: When compared to, steam technology was found to have an advantage over the 2-step procedure with cleaning and disinfection, because it avoids the use of chemicals, reduces water consumption, labor time and costs for cleaning.